Attitude Towards Reading of English Department Students in Darma Agung University: A Survey based on different personal attribute and environmental factors - Magdalena Marpaung; Humiras Betty Marlina Sihombing (JURNAL LITTERA: FAKULTAS SASTRA DARMA AGUNG, 2020)
The problems lies in this study are (1) how is the attitude towards reading of English Department students in Darma Agung University? (2) How is the attitude towards reading of English Department students in University of Darma Agung by the factors of (a) sex, (b) class type, (c) father’s education level, (d) mother’s education level, and (e) financial income level? After administered questionnaire of attitude towards reading by Gomleksiz (2004) to 46 students of English Department in Darma Agung University, there are findings found. First, the attitude towards reading of English Department students in Darma Agung University is mere positive for the average score of the 46 students is 143, 5 by the condition of the highest score is 172 and the lowest score is 111. Second, personal attributes and environmental factors are determine differences, the male students is mere positive in attitude towards reading by the average score of 145,4 than the female students by the average score of 142,6. In Class types, morning class students are having mere positive attitude towards reading by the average score of 147 than the evening class by the average score of 138,4. Fathers’ and mothers’ education level is also determining differences. However, mothers’ education level is affect linearly to the students attitude towards reading; the higher the mothers’ education level the mere positive the students’ attitude towards reading, but fathers’ education level is not affect the students attitude towards reading linearly. The last of the environmental factors, financial income level is linearly affect the students’ attitude towards reading; the higher the students’ financial income level the mere positive their attitude towards reading.